Pengukuran Tingkat Pengetahuan Keuangan Pelaku UMKM Kain Tenun Sa’dan - Jensi Sanda Pabisa; Marinus Ronal; Marchelin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research objective to be achieved is to determine the level of financial knowledge of Sa'dan Woven Fabric UMKM actors. This type of research uses a quantitative approach. The data collection technique is field research by distributing questionnaires. Instrument testing techniques are validity and reliability tests. Data were analyzed using Knowledge Level Criteria analysis. The results showed that the level of financial knowledge of Sa'dan Woven Fabric MSME players was classified into the low category.